Letter from Marianne Homburger to Max and Georg Bredig, March 10, 1941 - Homburger, Marianne (1941)
Marianne Homburger (1903-1987) writes a letter to her family in the U.S.A from Marseille, France, where is currently staying with other internees after being released from Gurs concentration camp. Marianne and her husband, Viktor Homburger (1888-1968), are waiting for information on ship departures and visas to the U.S.A. However, obtaining the visas could take several weeks, and all the available ship placements are already booked until the end of June. This slow progress worries Marianne, who fears the need to relocate if they don't succeed soon. In the letter, she also expresses concerns about their finances and luggage, and requests more updates from her father, Georg Bredig (1868-1944), and brother, Max Bredig (1902-1977).
Keywords: Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Jewish Holocaust (1939-1945); Emigration and immigration